If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(5x + -12) + 4(3x + 7) = 0 Reorder the terms: -1(-12 + 5x) + 4(3x + 7) = 0 (-12 * -1 + 5x * -1) + 4(3x + 7) = 0 (12 + -5x) + 4(3x + 7) = 0 Reorder the terms: 12 + -5x + 4(7 + 3x) = 0 12 + -5x + (7 * 4 + 3x * 4) = 0 12 + -5x + (28 + 12x) = 0 Reorder the terms: 12 + 28 + -5x + 12x = 0 Combine like terms: 12 + 28 = 40 40 + -5x + 12x = 0 Combine like terms: -5x + 12x = 7x 40 + 7x = 0 Solving 40 + 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + 7x = 0 + -40 Combine like terms: 40 + -40 = 0 0 + 7x = 0 + -40 7x = 0 + -40 Combine like terms: 0 + -40 = -40 7x = -40 Divide each side by '7'. x = -5.714285714 Simplifying x = -5.714285714
| 6=e/3 | | .144n=27 | | -9x+8=3x-4 | | 27.5n=17.16 | | 5x+19=43-7x | | 0=x+(4+3x)7 | | 8x-14+6x-2=180 | | 8x-14+6x-2= | | -10+x+x+4-5=7x-5 | | 3x+8y=23forx | | 4/1=11/c | | -9(5a-8)+(9q-6)= | | 4m-29=-28+3m | | 0=4+(8x+9)2 | | X^2+27x+169= | | 7s-7=-47+2s | | x^4+x^2-90= | | 40(x-20)=20(6) | | 7(1-8x)=7+2x | | 3x^5+3x^4-15x^3+6x^2=0 | | x-1/15=2/15 | | 0=x+5(5x+1) | | (y-2)(y+1)= | | x^6-90= | | x−1/15=2/15 | | 3=x3/3 | | 3=x/3/3 | | X^2+25x+141= | | x-1/10=615 | | 0=7(2+x)+6x | | x-1/24=5/24 | | 8x-7=x-7 |